Design of A Small Scale of Oceanic Wave Energy Converter At Terengganu Coast - Mohd Jaffar, Mohd Hafiz Helmi; Azlan, Hj. Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Wave energy has the highest energy density of all renewable energy sources and can generate more electrical power since the electrical power demand is increased every year. The main objective of this research is to design a wave energy converter that suitable to use in Malaysia. George E. Dieter design process is used as a framework for all actions, from defining problem to designing the details. Furthermore, SolidWorks software is used to conduct simulation and engineering drawings to analyses the product specification and shows that the model is workable to satisfy the necessity for energy production. The final design of the oceanic wave energy converter is planned to run the generator at 600 rpm to generate about 12kW of electrical power per day. By designing this wave energy converter that suitable for Malaysia wave condition, it will able to generate more electrical energy from ocean and be more effective.